Edukasi dan Deteksi Dini Pemeriksaan Tekanan Darah dalam Mencegah Risiko Komplikasi Hipertensi - Erjon Erjon; Ade Arinia Rasyad; Agnes Rendowaty; Nilda Lely; Masayu Azizah; Ema Ratna Sari; Dewi Patmayuni; Lilik Pranata; Masayu Rosyidah (Universitas 45 Surabaya, 2025)
Hypertension is one of the long-term conditions that can lead to serious complications. One of the best ways to reduce the risk of hypertension complications is to inform people about blood pressure checks and to have blood pressure checks early. Therefore, the purpose of the activity is to increase knowledge of early detection of blood pressure checks in preventing the risk of hypertension complications, the method of activity with education and blood pressure checks was carried out on Elementary Madrasah and Junior High School Teachers of the Ummul Quro Al-Hamidiyah Foundation Jl. Kyai Muara Ogan Mosque Kertapati Palembang, totaling 15 people on December 19, 2024. The results of the activity stated that teachers understand early detection of blood pressure checks in preventing the risk of hypertension complications. The conclusion of the activity stated that teachers' knowledge increased after direct evaluation after education and mentoring were carried out.